Longitudinal analysis of tear cathepsin S activity levels in male non-obese diabetic mice suggests its potential as an early stage biomarker of Sjögren's Syndrome. (2nd January 2019) - Janga, Srikanth R.; Shah, Mihir; Ju, Yaping; Meng, Zhen; Edman, Maria C.; Hamm-Alvarez, Sarah F.
Abstract: Context: Cathepsin S (CTSS) activity is elevated in Sjögren's Syndrome (SS) patient tears. Objective: To evaluate longitudinal expression of tear and tissue CTSS activity relative to other disease indicators in Non-Obese Diabetic (NOD) mice. Methods: CTSS activity was measured in tears and lacrimal glands (LG) from male 1–6 month (M) NOD and 1 and 6 M BALB/c mice. Lymphocytic infiltration was quantified by histopathology, while disease-related proteins (Rab3D, CTSS, collagen 1) were quantified using q-PCR and immunofluorescence. Results: In NOD LG, lymphocytic infiltration was noted by 2 M and established by 3 M ( p  < 0.01). IFN-ɣ, TNF-α, and MHC II expression were increased by 2 M ( p  < 0.01). Tear CTSS activity was significantly elevated at 2 M ( p  < 0.001) to a maximum of 10.1-fold by 6 M ( p  < 0.001). CTSS activity in LG lysates was significantly elevated by 2 M ( p  < 0.001) to a maximum of 14-fold by 3 M ( p  < 0.001). CTSS and Rab3D immunofluorescence were significantly increased and decreased maximally in LG acini by 3 M and 2 M, respectively. Comparable changes were not detected between 1 and 6 M BALB/c mouse LG, although Collagen 1 was decreased by 6 M in LG of both strains. Conclusion: Tear CTSS activity is elevated with other early disease indicators, suggesting potential as an early stage biomarker for SS.